2006
DOI: 10.1243/095441105x69060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hyaluronic acid on the time-dependent friction response of articular cartilage under different conditions

Abstract: Therapeutic lubricant injections of hyaluronic acid are a relatively recent treatment for osteoarthritis. Their efficacy, however, in vivo has been subject to much debate. Frictional properties of cartilage-cartilage contacts under both static and dynamic loading conditions have been investigated, using healthy cartilage and cartilage with a physically disrupted surface, with and without the addition of a therapeutic lubricant, hyaluronic acid. Most of the cartilage friction models produced typical time-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
98
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 14 publications
9
98
1
6
Order By: Relevance
“…The significant contribution of HA to the boundary lubrication of apposed articular cartilage surfaces reported here extends and clarifies the findings of previous studies examining the lubricating ability of HA with test protocols and/or configurations, particularly where a boundary mode of lubrication was dominant. Bell et al (16) demonstrated that Arthrease, a fermentation-derived sodium hyaluronate with an MW of 3,000 kd, functioned as an effective lubricant at a cartilage-cartilage interface, but only under static conditions in which the intrinsic biphasic lubrication was depleted. Despite the absolute values of static for both HA and PBS being ϳ3-fold less than those reported here, which may be attributable to differences in the test configuration and protocols, the study by Bell et al and the present study both show that HA contributes to boundary lubrication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant contribution of HA to the boundary lubrication of apposed articular cartilage surfaces reported here extends and clarifies the findings of previous studies examining the lubricating ability of HA with test protocols and/or configurations, particularly where a boundary mode of lubrication was dominant. Bell et al (16) demonstrated that Arthrease, a fermentation-derived sodium hyaluronate with an MW of 3,000 kd, functioned as an effective lubricant at a cartilage-cartilage interface, but only under static conditions in which the intrinsic biphasic lubrication was depleted. Despite the absolute values of static for both HA and PBS being ϳ3-fold less than those reported here, which may be attributable to differences in the test configuration and protocols, the study by Bell et al and the present study both show that HA contributes to boundary lubrication.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that HA may function by being retained at or between the articular cartilage surfaces under relative motion during testing. Such adsorbed layers of HA at the articular surface may have facilitated sliding (16), due to their inherent slipperiness and ease of disentangling (48), and therefore reduced friction between asperities in contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of hyaluronic acid to basic solution -PBS (Bell, 2006) or Ringers solution (Forsey, 2006) Svratka, Czech Republic, May 14 -17, 2018 Paper #320, pp. 709-712, doi: 10.21495/91-8-709 important.…”
Section: Introductionmentioning
confidence: 99%
“…Three types of boundary lubricant are considered to be involved, individually or in combination, in synovial joints, namely, hyaluronan (HA), lubricin and surface-active phospholipids (SAPLs) (Jay, 1992;Schwarz and Hills, 1998;Elsaid et al, 2005;Bell et al, 2006). Hyaluronan is an un-branched high-molecular-weight (500-3800 kDA, 1-4 mg/mL) anionic disaccharide consisting of alternating units of glucuronic acid b (1-3) and N-acetylglucosamine b (1-4) (Forsey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%